2020
DOI: 10.1016/j.redox.2020.101740
|View full text |Cite
|
Sign up to set email alerts
|

SOD2 deficiency in cardiomyocytes defines defective mitochondrial bioenergetics as a cause of lethal dilated cardiomyopathy

Abstract: Electrophilic aldehyde (4-hydroxynonenal; 4-HNE), formed after lipid peroxidation, is a mediator of mitochondrial dysfunction and implicated in both the pathogenesis and the progression of cardiovascular disease. Manganese superoxide dismutase (MnSOD), a nuclear-encoded antioxidant enzyme, catalyzes the dismutation of superoxide radicals (O 2 •- ) in mitochondria. To study the role of MnSOD in the myocardium, we generated a cardiomyocyte-specific SOD2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 58 publications
(69 reference statements)
2
38
0
Order By: Relevance
“…This is congruent with findings from Sod2 knockout mice which exhibit increased levels of oxygen reactive species with associated myocardial fibrosis and development of dilated cardiomyopathy. 26 Furthermore, we found an association between rheumatoid arthritis as well as baseline C-reactive protein (a well-established clinical inflammatory marker) with increased native myocardial T1 time emphasizing the role of inflammation in the propagation of myocardial interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is congruent with findings from Sod2 knockout mice which exhibit increased levels of oxygen reactive species with associated myocardial fibrosis and development of dilated cardiomyopathy. 26 Furthermore, we found an association between rheumatoid arthritis as well as baseline C-reactive protein (a well-established clinical inflammatory marker) with increased native myocardial T1 time emphasizing the role of inflammation in the propagation of myocardial interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 70%
“…SLC2A12 encodes solute facilitated glucose transporter member 12 (GLUT12), a basal and insulin-independent glucose transporter in the heart 22 with previously reported associations with heart failure, 23 diabetes, 24 and kidney disease. 25 Lead SNPs in SOD2 (rs6912979, P = 1.06×10 −10 ) and VEGFC (rs365843, P = 3.19×10 −9 ), two genes with established roles in cardiac hypertrophy and fibrosis in animal models, 26,27 were associated with decreased interventricular septum T1 times. Another lead SNP associated with interventricular septum T1 time is an intronic variant in ADAMTSL1 (rs1576900, P = 3.63×10 −11 ), a gene encoding an ADAMTS-like protein which is thought to modulate the function of ADAMTS metalloproteinases with integral roles in extracellular matrix turnover.…”
Section: Resultsmentioning
confidence: 99%
“…SOD1 overexpression leads to ROS scavenging and blocking production and block collagen production, suggesting that SOD1 may be a promising therapeutic agent for treating ROS-mediated cardiac fibrosis ( 25 ). Mice deficient in SOD2 die of cardiomyopathy within 10 days of birth, whereas heterozygous SOD2(+/–) mice show ultrastructural damage of the myocardium and mitochondria, associated with an increased oxidative stress as well as an activation of apoptotic signaling pathways in the heart ( 26 , 27 ). MnSOD overexpression offers protection against oxidative stress, fibrosis, and apoptosis in the aging heart ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sharma Sudha et al demonstrated that the absence of SOD2 leads to an increase in ROS ( Sharma et al, 2020 ). Nrf2 is widely recognized as a transcription factor activated by oxidative stress, and cells lacking Nrf2 can lead to mitochondrial dysfunction, resulting in increased ROS and impaired antioxidant capacity and further aggravated heart failure ( Tebay et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%